(untitled) (Journal of the College of Basic Education, 2022)
Protecting children from labor according to Iraqi laws and Islamic law In our world today, with great regret, we find a lack of interest in children, including their exploitation in work that is not commensurate with their ages, and because children are one of the goals of marriage, they must be protected due to the spread of child labor in a striking way in the world in general, and in roads in particular. Where Iraq has gone through accidents, disasters and wars in which the Iraqi family has lost, and since the eighties to this day their breadwinner by his death, loss, or disability that prevented him from performing his duty towards his family. Which prompted him to seek the help of his children, who did not reach the age of fifteen years, to occupy them in the simplest and most difficult work instead of him. After the Iraqi government was unable to fill the appointed vacancy by allocating subsidies to them, or giving them foodstuffs to fill their stomachs by activating the ration card, for example, or employing their children in special laboratories and under their supervision... Accordingly, I chose to have my research entitled (Protection of children in Iraqi laws and Islamic law) in order to be one of the contributors to the defense of children, and to explain their status and the role of Islamic laws and sharia in protecting them.